Application of Person‐Centered Analytic Methodology in Longitudinal Research: Exemplars From the Women's Health Initiative Clinical Trial Data. Issue 1 (11th December 2013) - Zaslavsky, Oleg; Cochrane, Barbara B.; Herting, Jerald R.; Thompson, Hilaire J.; Woods, Nancy F.; LaCroix, Andrea
Abstract Despite the variety of available analytic methods, longitudinal research in nursing has been dominated by use of a variable‐centered analytic approach. The purpose of this article is to present the utility of person‐centered methodology using a large cohort of American women 65 and older enrolled in the Women's Health Initiative Clinical Trial (N = 19, 891). Four distinct trajectories of energy/fatigue scores were identified. Levels of fatigue were closely linked to age, socio‐demographic factors, comorbidities, health behaviors, and poor sleep quality. These findings were consistent regardless of the methodological framework. Finally, we demonstrated that energy/fatigue levels predicted future hospitalization in non‐disabled elderly. Person‐centered methods provide unique opportunities to explore and statistically model the effects of longitudinal heterogeneity within a population. © 2013 Wiley Periodicals, Inc.